INTEGRATED TRADITIONAL CHINESE AND WESTERN MEDICINE FOR MENOPAUSAL SYNDROME: META-ANALYSIS OF RANDOMIZED CONTROLLED TRIALS - Liu, Yan; Ding, xiu-fang; Kou, mei-jing; Chen, jia-xu; Zou, xiao-juan; Jiang, Rui-xue; Dai, Hong (African Journal of Traditional, Complementary and Alternative Medicines, 2015)
Background: To critically assess the evidence of integrated Chinese and western medicine for treating Menopausal syndrome (MPS). Methods and Materials: A search across the Chinese Biomedical Medicine (CBM), Chinese National Knowledge Infrastructure (CNKI), VIP database (VIP), Wangfang database (Wanfang), PubMed and the Cochrane Library databases was conducted (up to October 31st, 2013) in commonly used integrated Chinese and western medicine therapies for menopausal syndrome. A number of Randomized Controlled Trials (RCTs) evaluating the therapeutic efficacy of integrated Chinese and western medicine in patients with PPS were included. The quality of the included studies was evaluated and a meta-analysis was performed using the RevMan5.0 software. Results: Twelve RCTs with 1155 patients were evaluated in this review. The results of meta-analysis showed that the therapy of using integrated Chinese and western medicine was significantly superior to that of western medicine alone towards improving the efficacy, relieving the clinical symptoms and decreasing follicle-stimulating hormone (FSH)levels (P<0.05), even though the effects of two treatments were the same in regulating the levels of luteinizing hormone (LH) and estradiol (E2). Conclusion: Compared to a regular treatment with western medicine alone, the therapeutic approach that utilizes integration of Chinese with western medicine can effectively improve the clinical efficacy and serum hormone levels in patients with menopausal syndrome. However, the evidence was not very strong due to the poor quality of the included studies.